KEANEKARAGAMAN SIMPLISIA NABATI DAN PRODUK OBAT TRADISIONAL YANG DIPERDAGANGKAN DI KABUPATEN PATI, JAWA TENGAH - Eri Irwanta; Agus Hikmat; Ervizal A.M. Zuhud (Media Konservasi, 2015)
Trend of medicinal plants use in Indonesia has increased along with the development of traditional medicine industries. It affects on the increasing demand for raw materials of traditional medicine in the form of simplisia. This research aimed to identify: vegetable simplisia, traditional medicine products, the selling price and source of simplisia traded in Pati regency, and assess the status of threat and rarity of the medicinal plant species. This research used direct observation and interview methods. Totally 126 of medicinal plant species that belongs to 55 families were recorded in this research. There were also 242 traditional medicine products from 40 indutries found on the market. The range of price of the cultivated simplisia was Rp 4.000,- – Rp 200.000,- per kilogram, while the wild simplisia was Rp 20.000,- – Rp 300.000,- per kilogram. Most simplisia were supplied from Semarang, Solo and surrounding area of each market. Furthermore, there were 8 species which included in the threatened category of LIPI; 2 species listed in Appendix II CITES; and 6 species of Least Concern category, and 1 species of Vulnerable category in IUCN Redlist. Keywords: medical plant, Pati Regency, simplisia, traditional medicine product